O-14 How do inpatient hospice volunteers view training as a means of preparing them for their role?. Issue Volume 7:Issue (2017)Supplement 2 (1st November 2017) - Dean, Antonia; Willis, Susan
Abstract : Background: There is a paucity of research on the training needs of hospice volunteers, despite acknowledgement that volunteers are crucial to the continued delivery of palliative care (Radbruch et al., 2010; Goosensen et al., 2016). The Commission into The Future of Hospice Care (2012) has called for a shared, core curriculum for the training of hospice volunteers but recognises the potential for unnecessary 'professionalisation' of volunteers, diluting their unique contribution. The volunteer perspective on training is not well-addressed in the literature. Aims: This study explores the views of UK inpatient hospice volunteers regarding initial training for role-preparation. Methods: A qualitative paradigm was selected with the aim of illuminating the volunteer experience. Data was collected by the audio-recording of two focus groups, with a combined total of 17 participants purposively recruited from volunteers working in a hospice inpatient unit. Thematic analysis was applied to transcripts of focus groups. Results: Six themes emerged: a) role preparation b) common sense and life experience c) role challenges, d) benefits and boundaries of training, e) training content, and f) training delivery. Volunteers perceived initial training to be important in increasing confidence and set out several areas where they felt additional training would be valuable. These included greeting and interacting with relatives, communication skills, cultural competence and the symptoms and signs of advanced illness. There was some disagreement about how training contributed to professionalisation and the extent of what education should be provided with respect to role boundaries. Volunteers advocated a mixed-methods approach to training, with an emphasis on scenario-based teaching and on-the-job mentoring and support. Conclusion: This study suggests areas of training that inpatient hospice volunteers perceive as worthwhile. It will inform local practice, shaping the education and support of future volunteers, and add to the wider evidence-base surrounding the development of this crucial group within the hospice workforce.